As propostas de autonomia mapuche no Chile do pós-ditadura (1990-2010) - Gomes, Caroline Faria (2020)
The Mapuche movement is currently a prominent social movement of indigenous origin in Chile and Latin America, composed of six main ethnic groups that mostly inhabit the southern regions of the country. The treatment directed to Mapuche by the Chilean Sta